Complete metric in the space of discontinuous functions - Banys, Rimas (Lietuvos matematikos rinkinys, 2000)
Complete metrics in the subspaces Dα, α > 0 of D[0, 1] which were introduced in [2] are given. These metrics are equivalent to the metrics dα defined in [2] and are stronger than the wellknown metric d in D[0,1] given in [1].